Early development and allometric growth patterns of the grumatã (Prochilodus vimboides Kner, 1859). Issue 3 (22nd July 2015) - Souza, Guilherme; Melo, Edésio J. T.; Caramaschi, Erica P.; Andrade, Dalcio R.; Monteiro, Leandro R.
Summary: The objective of this study was to characterize the early development and allometric growth of the grumatã ( Prochilodus vimboides ). We describe a sample of 266 eggs and larvae obtained through induced spawning. The eggs were spherical (mean 3.7 mm diameter), exhibited a yellow yolk and were non-adhesive and pelagic after fertilization and hydration. The time elapsed between the early cleavage and post-flexion stages was considered short (328 hours, 8054 hour-degrees) in regard to the development times of other Neotropical rheophilic species, but time to hatching was considerably longer than in other Prochilodus species. The most notable anatomical changes were observed between the end of the yolk larval stage and the beginning of the pre-flexion stage, when the larvae displayed directed swimming and the digestive system became functional, enabling the transition from endogenous to exogenous feeding. After hatching, the larvae grew from 6.04 to 15.15 mm in total length average. Two growth phases were observed at this stage: a non-linear asymptotic curve in yolk-sac larvae, and a linear constant-rate growth phase after exogenous feeding started. Allometric growth related to standard length was positive for head length, negative for eye diameter, and switched between phases from negative to positive in body depth and head height. Morphological development and allometric growth in different larval phases impose drastic anatomical and physiological changes that are synchronic with habitat changes and the flood cycles during the reproductive period.